Host and Bacterial Phenotype Variation in Adhesion of Streptococcus mutans to Matched Human Hosts - Esberg, Anders (American Society for Microbiology, 2012)
The commensal pathogen Streptococcus mutans uses AgI/II adhesins to adhere to gp340 adsorbed on teeth. Here we analyzed isolates of S. mutans (n = 70 isolates) from caries and caries-free human extremes (n = 19 subjects) by multilocus sequence typing (MLST), AgI/II full-length gene sequencing, and adhesion to parotid saliva matched from the strain donors (nested from a case-control sample of defined gp340 and acidic proline-rich protein [PRP] profiles). The concatenated MLST as well as AgI/II gene sequences showed unique sequence types between, and identical types within, the subjects. The matched adhesion levels ranged widely (40% adhesion range), from low to moderate to high, between subjects but were similar within subjects (or sequence types). In contrast, the adhesion avidity of the strains was narrow, normally distributed for high, moderate, or low adhesion reference saliva or pure gp340 regardless of the sequence type. The adhesion of S. mutans Ingbritt and matched isolates and saliva samples correlated (r = 0.929), suggesting that the host specify about four-fifths (r(2) = 0.86) of the variation in matched adhesion. Half of the variation in S. mutans Ingbritt adhesion to saliva from the caries cases-controls (n = 218) was explained by the primary gp340 receptor and PRP coreceptor composition. The isolates also varied, although less so, in adhesion to standardized saliva (18% adhesion range) and clustered into three major AgI/II groups (groups A, B(1), and B(2)) due to two variable V-region segments and diverse AgI/II sequence types due to a set of single-amino-acid substitutions. Isolates with AgI/II type A versus types B(1) and B(2) tended to differ in gp340 binding avidity and qualitative adhesion profiles for saliva gp340 phenotypes. In conclusion, the host saliva phenotype plays a more prominent role in S. mutans adhesion than anticipated previously.